MENTIMUN(Cucumis Sativus L) DI DESA TIRTA MULYA KECAMATAN MAKARTI JAYA KABUPATEN BANYUASIN II - Irham Falahudin; Elfira Rosa Pane; Esse Mawar (Biota, 2015)
Cucumber plants (Cucumis sativus L.) that includes or creeping vines and is one type of vegetable-fruit of the gourd family labuan (Cucurbitaceae) that has been popular throughout the world and favored from Asia. Cucumber cultivation in Indonesia, found almost in every region, ranging from lowland to highland hot climate (tropical) and moderate. One animal that has an abundant amount in cucumber plants are insects. This study aims to know the different types of species that exist on the Order Coleoptera cucumber farm in the village of Tirta Mulya District of makarti Jaya Banyuasin II and determine the role of the Order Coleoptera insects on cucumber plantations in the village of Tirta Mulya District of makarti Jaya Banyuasin II. This is a qualitative study conducted in October-November 2014 held in Cucumber Plants in the village of Tirta Mulya District of makarti Jaya Banyuasin II. Catching insects done using transect method and pitfall traps such as sweeping the net, pit fall traps and light traps, results in identification in the laboratory penelitanya UIN Raden Fatah Palembang. The results of this study indicate that insects are caught in a cucumber plantation obtained as many as 113 individual 3 families and 7 species. Insects which dominates in the village of Tirta Mulya District of makarti Jaya Banyuasin II is Cocinella repanda, Curinus coeruleus, Coelophora inaequalis, and Aulacophora similis, and insects that have the fewest number is Micraspis discolor, Micraspis vincta and Oryctes rhinoceros. The role of the Order Coleoptera Insects in general predators of the family Coccinellidae to eradicate mites while the family Chrysomelidae Scarabacidae and are pests that attack on cucumber plants that can cause death.